The clinical significance and prognostic implication of autophagy-related gene 13 in human gastric cancer - You, Yanjie; Li, Wenmei; Feng, Yudi; Gao, Ling; Li, Tiantian; Zhang, Xiaoli; Luo, Xiaomei (Frontiers in Oncology, 2026)
ObjectiveGastric cancer remains a leading cause of cancer-related death worldwide, underscoring the need for novel prognostic biomarkers to guide personalized therapy. Previous studies have identified that the autophagy-related gene 13 (ATG13) plays an essential role in cell biological processes, while its clinical significance and prognostic values in gastric cancer remain unclear.MethodsBioinformatic analyses were conducted to assess the transcription levels and genomic alterations of the ATG13 gene in gastric cancer. Immunohistochemistry was also utilized to evaluate the association between ZHX3 protein expression and clinicopathologic variables as well as patient survival. In addition, cell proliferation, colony formation and invasion assays were performed to examine the impacts of silencing ATG13 expression on gastric cancer cell growth and metastasis.ResultsATG13 expression was significantly elevated in gastric cancer tissues compared to noncancerous tissues, which was strongly associated with large tumor size and poor outcomes in patients with gastric cancer. Multivariate analysis indicated that ATG13 expression was an independent prognostic indicator for patient survival. Silencing ATG13 expression functionally inhibited growth and metastasis of gastric cancer cells.ConclusionThe above findings suggest that dysregulation of ATG13 expression is involved in gastric cancer progression and may serve as a candidate survival biomarker for this malignancy, which warrant further validation by further in vitro/in vivo models and clinical studies to strengthen the mechanistic evidence and translational potential in our future work.